Construction Scheme and Influence Analysis of Horizontal Small-Clear-Distance Shield Tunnel - Xujie Li; Hui Li; Yabin Cheng; Bing Zhang; Ming Qiao; Tao Yang (Buildings)
Based on the construction project of Guangzhou Metro Line 13, this paper explores the special construction scheme for the safety of horizontal small-clear-distance shield tunnel construction, which adopts the construction of a tunnel first and a station later in the actual project to reduce the impact on the tunnel segment and the existing bridge piles. At the same time, the MIDAS GTS(2022R1) geotechnical and structural finite element analysis software is used to simulate and analyze the shield excavation process by using the stratum–structure modeling method, and the effect of grouting reinforcement in the tunnel is compared and analyzed. Through the research and analysis of the displacement and deformation of the model, the rationality and effectiveness of grouting reinforcement are explored to ensure the smooth implementation of the special construction scheme. The test results show that the implementation of grouting reinforcement measures in the tunnel can effectively control the horizontal deformation of the existing bridge piles and the horizontal deformation of the left line segment of the small-clear-distance section, and the above two deformation indexes are reduced by 67.7% and 72.1%, respectively, compared with the non-reinforcement condition. The settlement deformation of the segment and the surrounding existing bridge piles meets the requirements of the code, so the construction scheme is basically feasible.